PERANCANGAN TATA LETAK ULANG (RELAYOUT) PABRIK TERHADAP TINGKAT PRODUKSI PRODUK BAKSO AYAM (Studi Kasus Pada Pabrik Bakso UD. Supra Dinasty Denpasar) - Al Haq, Zulkifly; Semadi Antara, Nyoman; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
This study aims to identify the actual condition of the UD. Supra Dynasty Denpasar in accordance with Good Manufacturing Practices (GMP) and redesigning the layout based on the results of the study as a recommendation. This study used a descriptive method, namely by providing objective explanation, comparison, and evaluation as a decision making authority. Data was collected through observation and interviews at the company. Data are collected, then the method of analysis From-To Chart is used to find the amount of raw materials that flow load (material flow) required in the production process in one day. Activity Relationship Chart (ARC) is used to get the layout planning based on the degree of linkage between space activities and existing facilities. All data have been collected was analyzed by using software Unequal Area Facility Layout Problems (UA-FLP) to facilitate the determination of optimum results. The Table of Productivity Cycle Time is used to determine the increase or decrease in productivity after relayout. The result showed that the new layout of the company could shorten the distance of material flow from 119,5 to 76,039 meters, and increasing the productivity was about 61,68%. Keywords : Good Manufacturing Practice (GMP), relayout, productivity.
Keywords: 45,